Business Strategy and the Management of Plateaued Employees - Slocum, John W.; Cron, William L.; Hansen, Richard W.; Rawlings, Sallie (Academy of Management Journal, 1985)
This study compared effective and ineffective plateaued salespersons in two companies having different business strategies in terms of their job histories, job satisfactions, perceived work environments, career stages, definitions of success, and career attitudes. The business strategy of the company had a significant effect on the incidence of plateauing and on the performance of the plateaued person.